DESAIN SISTEM OTOMATISASI POMPA MENGGUNAKAN PICOBOX DI PDAM KOTA DENPASAR - Uki Atmaja, Dewa Gede; Indra Partha, Cok Gede; Dyana Arjana, I Gede (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUM, 2020)
One of the uses of water resources can be done through the Regional Water Company (PDAM). Equipment needed in a water supply system that uses wells as a source of water include well pumps, booster pumps, and pump control systems so that the pumps can work effectively and efficiently. The Operation and Maintenance Section is still using a manual system in carrying out its duties by coming to the location and immediately conducting an inspection. This study designed a pump automation system with Aplus Massenger picobox tool using an SMS service. The pump automation system consists of a series of microcontrollers, GSM modules, RTC modules, and electric current sensors. SMS information on the value of the load current at the distribution substation is sent by the pump automation system according to the sensor reading information and the time information set on the system. The load current notification system can provide an SMS warning of a disturbance of the load current at the distribution substation. This pump automation system is carried out in the Treatment Room of the Water Treatment Pump Distribution Unit in the Denpasar City PDAM, with the result of an SMS reply in the form of "load current: 30-10-2019” is R = 64 Amperes, S = 63 Amperes, T = 64 Amperes to receive the information about the value of the load at the distribution substation.